The Role of Circadian Rhythmicity and CLOCK Genes in Psychiatry - Palm, Denise; Thome, Johannes (Pharmacopsychiatry, 2023)
Circadian rhythms are biological oscillations, that perpetuate themselves even in the absence of “zeitgebers” (external time cues), with a period of approximately 24 hours. The master pacemaker is the suprachiasmatic nucleus (SCN) of the hypothalamus. The SCN is entrained by environmental factors, particularly light, to the 24-hour light-dark cycle by the Earth’s rotation. Peripheral circadian oscillators, located in multiple cell types and tissues, are controlled by signals arising from the SCN and from the environment, particularly food intake, hormonal signals and body-temperature fluctuations. Circadian rhythmicity is observable in almost every cell of living organisms including humans and, for example in cell cultures, these rhythms persist even without the SCN 12.
Keywords: Attention-deficit/hyperactivity disorder(ADHD); Circadian rhythm; Molecular biology; Neurotransmitters; Fibroblast cell culture